Women's criminalisation and offending in Australia and New Zealand - Nagy, Victoria M.; Rychner, Georgina (Routledge studies in crime and society, 2024)
"Women's Criminalisation and Offending in Australia and New Zealand offers new research and analysis of women's offending and criminalisation in Australia and New Zealand from British settlement through to the late-twentieth/early twenty-first century. Drawing attention to women as offenders as understood in a multitude of ways, this collection highlights how women have been involved with crime and criminal behaviour, their treatment inside and outside of courts and prisons, and how women's deviation from societal norms have attracted negative attention throughout the decades. For Aboriginal and Māori women especially, the responses were harsher than what they could be for non-indigenous women. The chapters cover a broad range of transgressions that women have been actively involved with including theft, drug and alcohol abuse and offences, organised crime, and homicide, as well as how women's behaviour and their bodies have been criminalised and responded to by authorities. What this collection demonstrates is that women have often chosen to be involved with crime and criminality, while on other occasions their behaviour, innocent as it was, was not considered acceptable by contemporaries, resulting in confusion and misapprehension of women who refused to fit a mould. Women's Criminalisation and Offending in Australia and New Zealand brings together historical and criminological methods, theories, and scholars to shed light on how Australia and New Zealand colonial, later state and national governments have sought to understand, control, and punish women. This collection will be of interest and value to scholars, students, and everyone with an interest in Criminology, History, Law, Sociology, Indigenous Studies, and Australian and New Zealand Studies"--